Supervision and Monitoring with the Smart Patrol Method in the Marine Protected Area of the Gili Balu Marine Tourism Park - Rahmat Hidayatullah; Abdul Muis; Hernawati Hernawati; Tezar Refandi; Muslihuddin Aini; Sadikin Amir; Muhammad Haikal Abdurachman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The management of conservation areas includes surveillance and monitoring activities (patrols) carried out by supervisory community groups (pokmaswas) using the Smart Patrol method. Patrol activities aim to determine the utilization pattern and level of zoning compliance in the marine conservation area of Gili Balu Aquatic Tourism Park. Patrol activities are carried out in 2021 as many as 8 times with an average of 1 time every month. The average time used to make observations ±5 hours. During the activity, 32 points of utilization of capture fisheries were found by 36 fishermen. The composition of the fishing gear used is 78% fishing line, 10% drift gill nets, 9% squid angling, the remaining 3% arrows. Fishermen's catches are dominated by soft-skin animals (81%), small pelagic fish (16%), and reef fish (3%). The pressure level of TWP Gili Balu utilization is relatively high with the highest value found on Belang Island, which is 32 people per 4 km2. The compliance rate in the core zone is relatively high with a value of 81% and falls into the excellent category, as well as in the utilization zone it is quite high at 42% and belongs to the category of quite good. The level of knowledge or utilization of the Gili Balu TWP area is included in the sufficient (moderate) category, where 41% of users know about the existence of the Gili Balu TWP conservation area and 59% of people who do not know the existence of the Gili balu TWP conservation area and the rules in it. Pokmaswas who are actively involved in surveillance and monitoring activities are Pokmaswas Liang Kuru of Senayan village, Pokmaswas Bua Lawah of Poto Tano village. However, it is still necessary to carry out regular supervision and monitoring at locations that are prone to zoning violations and socialization related to the existence of the Gili Balu TWP conservation area and the zoning rules in it.